2016
DOI: 10.1021/acsmacrolett.5b00953
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Water-in-Water Emulsions by Nanorods

Abstract: Water-in-water (W/W) emulsions formed by mixing incompatible water-soluble polymers cannot be stabilized with molecular surfactants. However, they can be stabilized by particles through the so-called Pickering effect. Recently, it was shown that its stabilization can be achieved also with nanoplates. Here, we show for the first time that even nanorods in the form of cellulose nanocrystals (CNCs) can efficiently stabilize W/W emulsions. Static light scattering and confocal microscopy techniques were used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 19 publications
6
127
0
Order By: Relevance
“…Nanocrystalline celluloses have also been used as stabilizers of emulsions. 176,[181][182][183][184] However, in comparison with cellulose derivatives, the mechanisms are very different. Cellulose derivatives behave similarly to any flexible or semi-flexible amphiphilic polymer, like graft and block copolymers, and provide steric stabilization.…”
Section: Cellulose As a Dispersion Stabilizermentioning
confidence: 99%
“…Nanocrystalline celluloses have also been used as stabilizers of emulsions. 176,[181][182][183][184] However, in comparison with cellulose derivatives, the mechanisms are very different. Cellulose derivatives behave similarly to any flexible or semi-flexible amphiphilic polymer, like graft and block copolymers, and provide steric stabilization.…”
Section: Cellulose As a Dispersion Stabilizermentioning
confidence: 99%
“…The latter was explained by the formation of a weak gel of droplets connected by aggregated clay platelets. Peddireddy, Nicolai, Benyahia and Capron (2016) observed that P/D emulsions were stable when as little as 0.05 wt% cellulose nanocrystals (CNC) were added that have a highly anisotropic rectangular parallelepiped structure with average dimensions 160 nm × 6 nm × 6 nm. For such particles G depends on the length (l) and the width (b) of the particles:…”
Section: Effect Of the Particle Morphologymentioning
confidence: 99%
“…This has led severalg roups to describe such droplets as water-in-water (w/w) emulsions. Spherical colloidsw ith diameters typicallyg reater than 100 nm, including nanoparticles, [85,86] lipid vesicles [87,88] and protein clusters, [89] as well as high-aspect-ratio colloids, such as clays, [90] nanorods [91] or protein fibrils, [92] adsorb more effectively to interfaces with lows urface tension [92,93] and have therefore been used to stabiliseP EG/dextran aqueous two-phase systems (Figure 2D,E ), as well as complex coacervate droplets. Spherical colloidsw ith diameters typicallyg reater than 100 nm, including nanoparticles, [85,86] lipid vesicles [87,88] and protein clusters, [89] as well as high-aspect-ratio colloids, such as clays, [90] nanorods [91] or protein fibrils, [92] adsorb more effectively to interfaces with lows urface tension [92,93] and have therefore been used to stabiliseP EG/dextran aqueous two-phase systems (Figure 2D,E ), as well as complex coacervate droplets.…”
Section: Controlled Matter Exchangest Hrough Interfacial Membrane Assmentioning
confidence: 99%